Creep and Stress Relaxation of Geotextile-Reinforced Soils. Issue 4 (1998) - Helwany, S.M.B.; Shih, S.
Abstract : Creep and stress relaxation phenomena occur simultaneously in a geosynthetic-reinforced soil (GRS) structure. Therefore, the simultaneous measurement of creep and stress relaxation occurring in a soil-geosynthetic composite during long-term laboratory interaction tests is essential. This paper describes a new test apparatus that measures creep and stress relaxation simultaneously in soil-geotextile composites, which is essential for understanding the long-term interactive behavior between geosynthetic reinforcement layers and the confining soil.